Kehamilan Intraabdominal Usia 38 Minggu dengan Lahir Bayi Hidup - Cipta Pramana; Kartika Budi Peranawengrum; Renata Ekanindya Anggadewi (Universitas Sumatera Barat, 2025)
Abdominal pregnancy is a very rare form of ectopic pregnancy that carries life-threatening complications, in which the product of conception implants within the peritoneal cavity. The incidence is estimated to be approximately 1 in 10,000 to 30,000 live births, with high rates of maternal and perinatal morbidity and mortality. Because the clinical symptoms are nonspecific, diagnosis is often delayed, and ultrasonographic examination may fail to detect the abnormal implantation site. The aim of this study is to describe in detail the management of a case of intra-abdominal pregnancy. This research employs a descriptive method with a case report design, providing a detailed account of the diagnostic process, management, and clinical outcomes of a patient. The results report a rare case of a 28-year-old woman, gravida 2, with term intra-abdominal pregnancy who was treated at RSD K.R.M.T. Wongsonegoro Hospital, Semarang, Indonesia. The patient presented at 38 weeks of gestation with complaints of abdominal pain and transverse fetal lie. During laparotomy, an extrauterine pregnancy was discovered with an intact amniotic sac and a live male infant weighing 2980 grams with an excellent Apgar score. The placenta was attached to the abdominal wall, omentum, and the superior surface of the uterus, and was left in situ to prevent massive hemorrhage. The uterus and adnexa appeared normal. The postoperative course was uneventful, and follow-up examinations showed regression of the placental mass. The infant developed normally without any congenital abnormalities. This case provides an important lesson on the need for comprehensive clinical suspicion and early diagnosis through imaging to reduce maternal morbidity and mortality. Timely surgical intervention and a conservative approach to placental management are crucial for achieving favorable outcomes in cases of term abdominal pregnancy.